Hukum Jual Beli Buah Langsat dengan Sistem Jizāf (Studi Kasus di Posigadan Kabupaten Bolaang Mongondow Selatan) - Rosmita Rosmita; Muhammad Taufan Djafri; Maryam Mooduto; Nasaruddin Nasaruddin (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2022)
This study aims to understand the law of buying and selling langsat fruit with the jizāf system in Posigadan South Bolaang Mongondow Regency. The type of research is a case study (field research) using a normative, historical and sociological approach. The research results found are as follows. First, the practice of buying and selling langsat fruit with the jizāf system in Posigadan South Bolaang Mongondow Regency, which is bought by wholesale without being measured or mined again to traders when the langsat fruit is still on the tree and ready to be harvested. Second, the sale and purchase transactions of langsat fruit carried out by farmers and wholesalers in jizāf in Posigadan are legal in accordance with Islamic law because they have fulfilled the pillars of buying and selling, namely: the existence of sellers and buyers, objects of sale and purchase, and sighat. In addition, buying and selling transactions carried out by farmers and contractors have met the requirements of jizāf sale and purchase, namely: the merchandise is visible to the eye during the contract or before the contract, the seller and the buyer do not know the quantity of the merchandise, the purpose of buying and selling in jizaf is to buy in large quantities. many and not units, merchandise must be assessed by people who are experts in assessing, merchandise in large quantities but not too much, one contract may not include buying and selling where one object can be measured while the other cannot.